Antidiabetic activity of blood burnet extract in high fructose fed insulin resistant rats - Klevanova, Viktoriia; Trzhetsynskiy, Sergiy; Тржецинський, Сергій Дмитрович (USA: David Publishing Company, 2015)
Abstract: Insulin resistance is one of leading pathogenic process in diabetes mellitus type-2. It is known that high-fructose intake leads to obesity, diabetes, dyslipidemia in rodents. The aim of our study was to evaluate the effect of Blood burnet’s extract on body weight, visceral fat, blood glucose, plasma insulin, lipid profiles, lipid peroxidation and enzymatic antioxidants (superoxide dismutase, catalase, glutathione reductase) in fructose-induced type-2 diabetic rats. Our results showed that in high-fructose-induced diabetic rats were observed abdominal obesity, hyperglycemia, hyperinsulinemia, increased lipid profiles and atherogenic index, decreased insulin sensitivity, activation of lipid peroxidation and reduced activities of enzymatic antioxidants. Blood burnet’s extract was able to improve insulin resistance, glucose toleration, rectifies dyslipidemia and abolish the damage in antioxidant system in terms of high-fructose feeding in rats.
Keywords: Poterium sanguisorba L. Blood burnet; insulin resistance; fructose; rats